LEGALITAS SURAT KETERANGAN JUAL BELI TANAH YANG DIBUAT OLEH LURAH ATAU CAMAT - Ariandi Lumongga (UM.Tapanuli Selatan, 2024)
Certificates issued by the National Land Agency (BPN) have more legal strength compared to the Sale and Purchase Certificate of Land made by the village head or sub-district head. Most of these unregistered lands are located in rural and urban settlement areas; however, the residents have occupied the land for a long time, and land ownership rights can only be proven with a land certificate issued by the village head or sub-district head. In a sales transaction, both parties rely on each other's trust. The research method used is empirical juridical legal research. The research results show that the legality of the sale and purchase certificate for land is valid and has strong legal force as long as there are no higher regulations governing it. However, with the enactment of Law Number 5 of 1960 concerning the Basic Agrarian Law (UUPA), the legal status of the sale and purchase certificate for land became weak and no longer had legal force.